2020
DOI: 10.1186/s13620-020-00168-w
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study on calf diarrhea and coccidiosis in dairy farms in Bahir Dar, North West Ethiopia

Abstract: Background: A longitudinal prospective study was conducted from October 2017 to April 2018 on calf diarrhea and coccidiosis in dairy farms in Bahir Dar, North West Ethiopia with the objectives of determining the incidence of calf diarrhea and calf coccidiosis from diarrheic calves, assessing the major risk factors associated with calf diarrhea and coccidiosis and identifying the existing Eimeria species. A total of 237 calves, 86 calves from 52 smallholder dairy farms and 151 calves from 8 large dairy farms, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 18 publications
5
21
3
Order By: Relevance
“…10 The present prevalence of sheep Eimeria infection (58.0%) was lower than 66.8% prevalence in Bishoftu and central Ethiopia 10,11 and 62.7% in and around Haramaya, Eastern Hararghe, Ethiopia, 43,46 68.3% prevalence reported from Brazil, 56 97.5% in Tanzania, 31,32 91.5% in Western Iran, 30 92.9% in Northeastern China. 2 However, the present prevalence of sheep Eimeria infection was higher than the one reported by 35,60 (22.4%) in Addis Zemen, Gondar, Ethiopia and also higher than the report from India (12.7%). 54 The present prevalence of both cattle and sheep Eimeria infection (48.95%) was lower than 57.3% prevalence recorded in Akaki Kality Subcity of Addis Ababa.…”
Section: Discussioncontrasting
confidence: 75%
“…10 The present prevalence of sheep Eimeria infection (58.0%) was lower than 66.8% prevalence in Bishoftu and central Ethiopia 10,11 and 62.7% in and around Haramaya, Eastern Hararghe, Ethiopia, 43,46 68.3% prevalence reported from Brazil, 56 97.5% in Tanzania, 31,32 91.5% in Western Iran, 30 92.9% in Northeastern China. 2 However, the present prevalence of sheep Eimeria infection was higher than the one reported by 35,60 (22.4%) in Addis Zemen, Gondar, Ethiopia and also higher than the report from India (12.7%). 54 The present prevalence of both cattle and sheep Eimeria infection (48.95%) was lower than 57.3% prevalence recorded in Akaki Kality Subcity of Addis Ababa.…”
Section: Discussioncontrasting
confidence: 75%
“…However, the prevalence shown in this analysis is below compared with other studies made in MĂ©xico with cattle (60.2%) (Alcala-Canto et al, 2020) and other countries such as Brazil (66%) (FloriĂŁo et al, 2016), Indonesia (65.4%), (Ekawasti et al, 2022), Iran (63%) (Adinehbeigi et al, 2018) and Colombia (75.6%) (Lopez-Osorio et al, 2020). This variation is most likely attributed to the differences in study design, biotic and abiotic factors and husbandry practices of the study animals in different countries (Tamrat et al, 2020), a high animal density, accumulation of organic material and mix of animals of different ages (FloriĂŁo et al, 2016). On the other hand, in this study, a high prevalence was observed in the physiographic region of "Nautla" with 48.8%.…”
Section: Discussionmentioning
confidence: 56%
“…The proportion of both Nematode (OR=5.7, p< 0.05) and Eimeria species (OR=5.3, P< 0.05) infection was significantly higher in diarrheic calves than calves with normal faeces consistency. In dairy farms diarrhea was most frequently observed disorder in various parts (Tamrat et al, 2020;Ć»ychliƄska-Buczek et al, 2015;Megersa et al, 2009;Wudu et al, 2008). It is known that some Nematodes species and Eimeria species known to damage the intestinal epithelial cells leading to inflammation and cause diarrhea (Constable et al, 1017;Ramadan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%